Eco-effective Sustainable Risk Assessment Model for homogeneous solid waste mortars based on the Cradle to Cradle paradigm - Cadenas, Nigme; Vásquez Stanescu, Carmen Luisa; Gómez-Caicedo, Melva Inés; Gaitan-Angulo, Mercedes; Briñez Torres, Carlos Yesid (Frontiers in Sustainability, 2023)
The unrestricted use of non-renewable natural resources in masonry mortars and the rapid increase in solid waste on the planet contribute to the deterioration of the environment. It is a priority for the United Nations to promote growth without compromising the ability of new generations to attend to their own, for this purpose 17 Sustainable Development Goals of faithful compliance for all countries are formulated. The present work arises from the need to propose a model to evaluate in the design phase, the homogeneous solid waste, total or partial substitute of some of the components of the mortars in the construction sector, based on the Cradle to Cradle paradigm with the objective of including improved materials for the health of living beings and the environment, by establishing a circular system in the manufacture of mortars including only safe and healthy materials that can be reused with the guarantee of not affecting the health of living beings and to the environment, contributing to sustainability. Based on the positivist epistemological current; projective research with documentary design, begins by analyzing scientific publications that recommend the use of solid waste only in the verification of its rheological properties, ignoring how the inclusion of this material can affect living beings and the environment; it is contrasted with the results of published public access research regarding the chemical substances that make up said material; Next, the eco-effective model is designed and its application is validated, managing to identify in the waste of the selected cases, the potential risks for the health of living and environmental beings, recommending avoiding the recycling of those materials that cause concern, to finally contribute with improved mortar designs for living beings and the planet, minimizing the use of natural resources and increasing productivity in the field of construction, implementing this vision through continuous development and improvement.